Evaluation of the efficacy of the Lentulo spiral filler operated at four different speeds and with two different techniques in cadaveric canine teeth of dogs - Carlson, Haley; Montebello, Jennifer; Lee, Bonnie; Rendahl, Aaron; Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2023)
This study evaluated the effect of filling technique and rotational speed on the efficacy of sealer cement placement using the Lentulo spiral filler. Cadaveric maxillary and mandibular canine teeth (n=74) from age and breed matched fresh-frozen adult canine cadaver heads were utilized.Following routine mechano-chemical preparation, teeth were randomly divided into 8 treatment groups with varying rotational speeds (250-2,000 revolutions per minute (RPM)) and fill techniques (backfill technique versus pumping technique). The quality of the sealer cement fill was evaluated radiographically before and after master gutta percha cone placement. Percentage of voids present in the apical, midbody, and coronal portions of the tooth were subjectively scored as: no voids present, voids present in less than 25% of the area, voids present in 25-50% of the area, voids present in greater than 50% of the area. The apex was also scored as underfilled, adequately filled, or overfilled. Operating the Lentulo spiral filler at 2,000 RPM resulted in the best quality fill regardless of filling technique. The pumping technique with placement of the master gutta percha cone had a higher probability of success as compared to the backfill technique, but this finding lacked significance. Regardless of speed or technique, the apical region had the highest quality of fill. The addition of the master gutta percha cone improved the quality of fill. Therefore, we recommend using the Lentulo spiral filler at higher speeds with a pumping technique (followed by addition of a master gutta percha cone) to improve the quality of epoxy resin-based sealer cement placement.